Negative electrode binder, negative electrode plate and electrochemical energy storage device
By using the negative electrode binder with a core-shell structure in lithium-ion batteries, the problem of insufficient expansion suppression and dispersion of the negative electrode material is solved, the cycle performance and structural stability of the battery are improved, and the service life of the battery is extended.
Patent Information
- Application Number
- CN202411849713.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The negative electrode binder of the existing lithium-ion battery has insufficient ability to suppress the expansion of graphite active substances and silicon-carbon negative electrode materials during the charging and discharging process, resulting in a short battery cycle life and is not conducive to the uniform dispersion of the negative electrode active substances and conductive agents.
Using a negative electrode binder with a core-shell structure, the core layer consists of monomers such as orthophenylphenoxyethylacrylate, and the shell layer consists of monomers such as unsaturated sulfonates and hydroxyesters, and the core is controlled by controlling the core. The ratio, diameter and glass transition temperature of the layer to the shell are used to form a binder with good flexibility and dispersion.
Effectively suppress the volume expansion of the negative electrode material, improve the circulation performance and structural stability of the battery, and extend the circulation life of the battery.
Smart Images

Figure CN119307207A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical technology, and specifically relates to a negative electrode binder, a negative electrode plate and an electrochemical energy storage device, and in particular to a negative electrode binder for a lithium ion secondary battery. Background Art
[0002] Lithium-ion batteries are widely used due to their advantages such as high mass energy density, high volume energy density and long cycle life. Their application range includes electronic products such as laptops, mobile phones or digital products, as well as power batteries such as electric vehicles or energy storage power stations.
[0003] The electrode binder adheres to the surface of the current collector and provides strong bonding force to maintain the integrity of the electrode structure, thereby ensuring that the lithium-ion battery can be charged and discharged normally. The performance of the electrode binder directly affects the electrochemical performance of the battery. At present, the commercial negative electrode binder is mainly styrene butadiene rubber binder (SBR). The existing styrene butadiene rubber binder has good elasticity and adhesion, and can provide good electrode bonding and electrode flexibility; however, the elastic modulus is small and the anti-expansion ability is weak. It has poor expansion inhibition effect on graphite active substances and silicon-carbon negative electrode materials, and is not conducive to the uniform dispersion of negative electrode active substances and conductive agents. Summary of the invention
[0004] In order to solve the above problems, the object of the present invention is to provide a negative electrode binder for preparing a negative electrode sheet of an electrochemical energy storage device such as a lithium ion secondary battery.
[0005] The technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a negative electrode binder, wherein the negative electrode binder has a core-shell structure, wherein the core-shell structure consists of a core layer and a shell layer, wherein the shell layer covers the core layer; Wherein, the core layer monomer used to synthesize the core layer includes: o-phenylphenoxyethyl acrylate.
[0006] In some embodiments, the core layer monomers used to synthesize the core layer include: o-phenylphenoxyethyl acrylate, and at least two or at least three of acrylonitrile, unsaturated carboxylic acid, acrylate, unsaturated amide, and styrene. The shell monomers used to synthesize the shell layer include at least two or at least three of unsaturated sulfonates, unsaturated hydroxy esters, unsaturated carboxylic acids, unsaturated sulfonates, unsaturated amides, unsaturated phosphates, and other monomers; In some embodiments, the unsaturated carboxylic acid is selected from at least one of acrylic acid, methacrylic acid, ethyl acrylic acid, propyl acrylic acid, isopropyl acrylic acid, n-butyl acrylic acid, isobutyl acrylic acid, tert-butyl acrylic acid, cyclopropyl acrylic acid, n-pentyl acrylic acid, isopentyl acrylic acid, cyclopentyl acrylic acid, n-hexyl acrylic acid, isohexyl acrylic acid, and cyclohexyl acrylic acid; and / or The acrylic acid ester is selected from at least one of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, cyclopropyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate, lauryl methacrylate, glycidyl methacrylate, tert-butylaminoethyl methacrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl acrylate, vinyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, phenyl methacrylate, dodecyl methacrylate, and hexadecyl methacrylate; and / or The unsaturated amides are selected from at least one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, N-methyl acrylamide and N-hydroxymethyl methacrylamide; and / or The unsaturated sulfonate is selected from at least one of styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, methyl allyl sulfonate, allyl sulfonate, and methacrylamide isopropyl sulfonate; and / or The unsaturated sulfonate is selected from at least one of methyl styrene sulfonate, ethyl styrene sulfonate, propyl styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, allyl sulfonate, methyl allyl sulfonate, and methacrylamide isopropyl sulfonate; and / or The unsaturated hydroxy ester is selected from at least one of β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, bis(2-hydroxyethyl)maleate, and 2-hydroxyethyl methyl fumarate; and / or The unsaturated phosphate is selected from at least one of di(2-methacryloyloxyethyl)phosphate, 2-hydroxyethyl methacrylate phosphate, 2-hydroxyethyl acrylate phosphate, and allyl polyether phosphate; and / or The other monomers are selected from at least one of polyethylene glycol acrylate, vinyl pyridine, vinyl pyrrolidone, polyethylene glycol methacrylate, ethylene glycol dimethacrylate, β-carboxyethyl acrylate, sodium 1-allyloxy-2-hydroxypropyl sulfonate, and diallyl maleate.
[0007] In some embodiments, the raw materials for preparing the negative electrode binder include: a core layer monomer for synthesizing the core layer, a shell layer monomer for synthesizing the shell layer, an initiator, an emulsifier and water; Wherein, the weight ratio of the shell monomer to the core monomer is (0.13-0.52): 1, or Based on 200 parts by weight of the total weight of the shell layer monomer and the core layer monomer, the weight of the emulsifier is 8-15 parts, or Based on the total weight of the shell layer monomer and the core layer monomer being 200 parts, the weight of the initiator is 10 parts, or Based on 200 parts by total weight of the shell layer monomer and the core layer monomer, the weight of the water is 500-1000 parts.
[0008] In some embodiments, the diameter of the core layer is 50-500 nm and the thickness of the shell layer is 1-10 nm; and / or The glass transition temperature of the core layer is -20°C to 20°C, and the glass transition temperature of the shell layer is 80°C to 160°C; and / or The swelling degree of the core layer in the electrolyte is 20%-200%, and the swelling degree of the shell layer in the electrolyte is 1%-10%.
[0009] In some embodiments, the glass transition temperature of the shell layer is greater than the glass transition temperature of the core layer; and / or The negative electrode binder is used to prepare a secondary battery, and the secondary battery includes a lithium ion battery or a sodium ion battery.
[0010] In a second aspect, the present invention provides another negative electrode binder, wherein the negative electrode binder has a core-shell structure, wherein the core-shell structure consists of a core layer and a shell layer, wherein the shell layer covers the core layer; wherein the diameter of the core layer is 50-500 nm, the thickness of the shell layer is 1-10 nm, or The glass transition temperature of the shell layer is greater than the glass transition temperature of the core layer, or The swelling degree of the core layer in the electrolyte is 20%-200%, and the swelling degree of the shell layer in the electrolyte is 1%-10%.
[0011] In some embodiments, the diameter of the core layer is 50-500 nm and the thickness of the shell layer is 1-10 nm; and / or The glass transition temperature of the core layer is -20°C to 20°C, and the glass transition temperature of the shell layer is 80°C to 160°C; and / or The swelling range of the core layer in the electrolyte is 20%-200%, and the swelling range of the shell layer in the electrolyte is 1%-10%.
[0012] In some embodiments, the diameter of the core layer is 100-300 nm and the thickness of the shell layer is 5-10 nm; and / or The glass transition temperature of the core layer is -10°C to 10°C, and the glass transition temperature of the shell layer is 100°C to 140°C; and / or The swelling range of the core layer in the electrolyte is 30%-100%, and the swelling range of the shell layer in the electrolyte is 1%-8%.
[0013] In some embodiments, the core layer monomer used to synthesize the core layer includes: o-phenylphenoxyethyl acrylate.
[0014] In some embodiments, the core layer monomers used to synthesize the core layer include: o-phenylphenoxyethyl acrylate, and at least two or at least three of acrylonitrile, unsaturated carboxylic acid, acrylate, unsaturated amide, and styrene, or The shell monomers used to synthesize the shell layer include at least two or at least three of unsaturated sulfonates, unsaturated hydroxy esters, unsaturated carboxylic acids, unsaturated sulfonates, unsaturated amides, unsaturated phosphates, and other monomers.
[0015] In some embodiments, the unsaturated carboxylic acid is selected from at least one of acrylic acid, methacrylic acid, ethyl acrylic acid, propyl acrylic acid, isopropyl acrylic acid, n-butyl acrylic acid, isobutyl acrylic acid, tert-butyl acrylic acid, cyclopropyl acrylic acid, n-pentyl acrylic acid, isopentyl acrylic acid, cyclopentyl acrylic acid, n-hexyl acrylic acid, isohexyl acrylic acid, and cyclohexyl acrylic acid; and / or The acrylic acid ester is selected from at least one of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, cyclopropyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate, lauryl methacrylate, glycidyl methacrylate, tert-butylaminoethyl methacrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl acrylate, vinyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, phenyl methacrylate, dodecyl methacrylate, and hexadecyl methacrylate; and / or The unsaturated amides are selected from at least one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, N-methyl acrylamide and N-hydroxymethyl methacrylamide; and / or The unsaturated sulfonate is selected from at least one of styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, allyl sulfonate, methyl allyl sulfonate, and methacrylamide isopropyl sulfonate; and / or The unsaturated sulfonate is selected from at least one of methyl styrene sulfonate, ethyl styrene sulfonate, propyl styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, allyl sulfonate, methyl allyl sulfonate, and methacrylamide isopropyl sulfonate; and / or The unsaturated hydroxy ester is selected from at least one of β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, bis(2-hydroxyethyl)maleate, and 2-hydroxyethyl methyl fumarate; and / or The unsaturated phosphate is selected from at least one of di(2-methacryloyloxyethyl)phosphate, 2-hydroxyethyl methacrylate phosphate, 2-hydroxyethyl acrylate phosphate, and allyl polyether phosphate; and / or The other monomers are selected from at least one of polyethylene glycol acrylate, vinyl pyridine, vinyl pyrrolidone, polyethylene glycol methacrylate, ethylene glycol dimethacrylate, β-carboxyethyl acrylate, sodium 1-allyloxy-2-hydroxypropyl sulfonate, and diallyl maleate.
[0016] In some embodiments, the negative electrode binder is used to prepare a secondary battery, and the secondary battery includes a lithium ion battery or a sodium ion battery.
[0017] In some embodiments, the raw materials for preparing the negative electrode binder include: a core layer monomer for synthesizing the core layer, a shell layer monomer for synthesizing the shell layer, an initiator, an emulsifier and water; Wherein, the weight ratio of the shell monomer to the core monomer is (0.13-0.52): 1, or Based on 200 parts by weight of the total weight of the shell layer monomer and the core layer monomer, the weight of the emulsifier is 8-15 parts, or Based on the total weight of the shell layer monomer and the core layer monomer being 200 parts, the weight of the initiator is 10 parts, or Based on 200 parts by total weight of the shell layer monomer and the core layer monomer, the weight of the water is 500-1000 parts.
[0018] In a third aspect, the present invention further provides a negative electrode plate, on which the negative electrode plate is loaded with the negative electrode binder.
[0019] In a fourth aspect, the present invention provides an electrochemical energy storage device, comprising: the aforementioned negative electrode binder, or the aforementioned negative electrode plate.
[0020] In some embodiments, the electrochemical energy storage device comprises a secondary battery comprising a lithium ion battery or a sodium ion battery.
[0021] Compared with the prior art, the present invention has the following effects: The negative electrode binder has good flexibility, dispersibility, mechanical modulus and bonding strength, which is beneficial to inhibiting the volume expansion of the negative electrode active material during the charge and discharge process, and is also beneficial to maintaining structural stability during long cycles, thereby improving the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of the core-shell structure of the negative electrode binder provided in an embodiment of the present invention; Figure 2 The chemical structure of one of the polymer monomers used to synthesize the core layer in an embodiment of the present invention. DETAILED DESCRIPTION
[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0024] In a first aspect, an embodiment of the present invention provides a negative electrode binder, wherein the negative electrode binder has a core-shell structure, wherein the core-shell structure is composed of a core layer and a shell layer, and the shell layer covers the core layer; Wherein, the core layer monomer used to synthesize the core layer includes: o-phenylphenoxyethyl acrylate.
[0025] In some embodiments, the core layer monomers used to synthesize the core layer include: o-phenylphenoxyethyl acrylate, and at least two or at least three of acrylonitrile, unsaturated carboxylic acid, acrylate, unsaturated amide, and styrene. The shell monomers used to synthesize the shell layer include at least two or at least three of unsaturated sulfonates, unsaturated hydroxy esters, unsaturated carboxylic acids, unsaturated sulfonates, unsaturated amides, unsaturated phosphates, and other monomers.
[0026] In the embodiments of the present invention, a monomer refers to a small molecule organic compound that is polymerized by chemical reaction to form a polymer. For the convenience of expression, a "polymer monomer" is sometimes referred to as a "monomer", that is, "core layer monomers for synthesizing the core layer", "core layer polymer monomers", "core layer polymer monomers", "core layer monomers" are the same type of substances, and similarly, "shell layer monomers for synthesizing the shell layer", "shell layer polymer monomers", "shell layer polymer monomers", "shell layer monomers" are the same type of substances.
[0027] In some embodiments, the above unsaturated carboxylic acids are selected from at least one of acrylic acid, methacrylic acid, ethyl acrylic acid, propyl acrylic acid, isopropyl acrylic acid, n-butyl acrylic acid, isobutyl acrylic acid, tert-butyl acrylic acid, cyclopropyl acrylic acid, n-pentyl acrylic acid, isopentyl acrylic acid, cyclopentyl acrylic acid, n-hexyl acrylic acid, isohexyl acrylic acid, and cyclohexyl acrylic acid.
[0028] In some embodiments, the above acrylates are selected from at least one of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, cyclopropyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate, lauryl methacrylate, glycidyl methacrylate, tert-butylaminoethyl methacrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl acrylate, vinyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, phenyl methacrylate, dodecyl methacrylate, and hexadecyl methacrylate.
[0029] In some embodiments, the above unsaturated amides are selected from at least one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, N-methyl acrylamide, and N-hydroxymethyl methacrylamide.
[0030] In some embodiments, the above unsaturated sulfonates are selected from at least one of styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, allyl sulfonate, methallyl sulfonate, and methacrylamide isopropyl sulfonate.
[0031] In some embodiments, the above unsaturated sulfonates are selected from at least one of methyl styrene sulfonate, ethyl styrene sulfonate, propyl styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, allyl sulfonate, methyl allyl sulfonate, and methacrylamide isopropyl sulfonate.
[0032] In some embodiments, the above unsaturated hydroxy ester is selected from at least one of β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, bis(2-hydroxyethyl)maleate, and 2-hydroxyethyl methyl fumarate.
[0033] In some embodiments, the above unsaturated phosphates are selected from at least one of di(2-methacryloyloxyethyl)phosphate, 2-hydroxyethyl methacrylate phosphate, 2-hydroxyethyl acrylate phosphate, and allyl polyether phosphate.
[0034] In some embodiments, the above other monomers are selected from at least one of polyethylene glycol acrylate, vinyl pyridine, vinyl pyrrolidone, polyethylene glycol methacrylate, ethylene glycol dimethacrylate, β-carboxy ethyl acrylate, sodium 1-allyloxy-2-hydroxypropyl sulfonate, and diallyl maleate.
[0035] In some embodiments, the raw materials for preparing the negative electrode binder include: a core layer monomer for synthesizing the core layer, a shell layer monomer for synthesizing the shell layer, an initiator, an emulsifier and water. Wherein, the weight ratio of the shell monomer to the core monomer is (0.13-0.52): 1, or Based on 200 parts by weight of the total weight of the shell layer monomer and the core layer monomer, the weight of the emulsifier is 8-15 parts, or Based on the total weight of the shell layer monomer and the core layer monomer being 200 parts, the weight of the initiator is 10 parts, or Based on 200 parts by total weight of the shell layer monomer and the core layer monomer, the weight of the water is 500-1000 parts.
[0036] By controlling the relative amounts of raw materials such as the core layer monomer used to synthesize the core layer, the shell layer monomer used to synthesize the shell layer, the initiator, the emulsifier and water, the parameters such as the glass transition temperature of the negative electrode binder and the degree of swelling in the electrolyte are ensured to be within the specified range, so that the negative electrode binder has good electrical properties.
[0037] In a further embodiment, the preparation method of the above-mentioned inorganic binder comprises the following steps: (1) adding a core layer monomer to an aqueous solution containing an emulsifier, mixing and heating the mixture once, and adding an initiator to react the mixture once; (2) Pre-emulsifying the shell monomer, emulsifier and water. After the pre-emulsification, add the pre-emulsified liquid and the aqueous solution of the initiator to the reaction product of (1) for secondary reaction. After cooling, the following is obtained: Figure 1 The negative electrode binder shown has a core-shell structure.
[0038] In some embodiments, the diameter of the core layer is 50-500 nm, and the thickness of the shell layer is 1-10 nm. In some specific embodiments, the diameter of the core layer is 50nm, 75nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 330nm, 350nm, 380nm, 400nm, 430nm, 450nm, 470nm or 500nm. In some specific embodiments, the thickness of the shell layer is 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm or 10nm.
[0039] In some embodiments, the glass transition temperature of the shell layer is greater than the glass transition temperature of the core layer.
[0040] In some embodiments, the glass transition temperature of the core layer is -20°C to 20°C, and the glass transition temperature of the shell layer is 80°C to 160°C. In some specific embodiments, the glass transition temperature of the core layer is -20°C, -19°C, -18°C, -17°C, -16°C, -15°C, -14°C, -13°C, -12°C, -11°C, -10°C, -9°C, -8°C, -7°C, -6°C, -5°C, -4°C, -3°C, -2°C, -1°C, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 16°C, 17°C, 18°C, 19°C or 20°C. In some specific embodiments, the glass transition temperature of the shell layer is 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C or 160°C.
[0041] In some embodiments, the swelling degree of the core layer in the electrolyte is 20%-200%, and the swelling degree of the shell layer in the electrolyte is 1%-10%. In some specific embodiments, the swelling degree of the core layer in the electrolyte is 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190% or 200%. In some specific embodiments, the swelling degree of the shell layer in the electrolyte is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0042] In some embodiments, the negative electrode binder is used to prepare a secondary battery, and the secondary battery includes a lithium ion battery or a sodium ion battery.
[0043] In some embodiments, the negative electrode binder forms a negative electrode with a negative electrode collector, a negative electrode material, and a conductive agent, or the negative electrode binder forms a negative electrode sheet with a negative electrode collector, a negative electrode material, a conductive agent, and a thickener.
[0044] In some embodiments, the negative electrode material is graphite, the conductive agent is Super-P, and the thickener is carboxymethyl cellulose.
[0045] In a second aspect, an embodiment of the present invention provides another negative electrode binder, wherein the negative electrode binder has a core-shell structure, wherein the core-shell structure is composed of a core layer and a shell layer, wherein the shell layer covers the core layer. wherein the diameter of the core layer is 50-500 nm, the thickness of the shell layer is 1-10 nm, or The glass transition temperature of the shell layer is greater than the glass transition temperature of the core layer, or The swelling degree of the core layer in the electrolyte is 20%-200%, and the swelling degree of the shell layer in the electrolyte is 1%-10%.
[0046] In some specific embodiments, the diameter of the core layer is 50nm, 75nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 330nm, 350nm, 380nm, 400nm, 430nm, 450nm, 470nm or 500nm.
[0047] In some specific embodiments, the shell layer has a thickness of 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, or 10 nm.
[0048] In some embodiments, the glass transition temperature of the core layer is -20°C to 20°C, and the glass transition temperature of the shell layer is 80°C to 160°C. In some specific embodiments, the glass transition temperature of the core layer is -20°C, -19°C, -18°C, -17°C, -16°C, -15°C, -14°C, -13°C, -12°C, -11°C, -10°C, -9°C, -8°C, -7°C, -6°C, -5°C, -4°C, -3°C, -2°C, -1°C, 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, 16°C, 17°C, 18°C, 19°C or 20°C. In some specific embodiments, the glass transition temperature of the shell layer is 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C or 160°C.
[0049] In some specific embodiments, the degree of swelling of the core layer in the electrolyte is 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190% or 200%.
[0050] In some specific embodiments, the degree of swelling of the shell in the electrolyte is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0051] In some embodiments, the core layer monomers used to synthesize the core layer include: o-phenylphenoxyethyl acrylate; Optionally, the diameter of the core layer is 100-300 nm, and the thickness of the shell layer is 5-10 nm; and / or The glass transition temperature of the core layer is -10°C to 10°C, and the glass transition temperature of the shell layer is 100°C to 140°C; and / or The swelling range of the core layer in the electrolyte is 30%-100%, and the swelling range of the shell layer in the electrolyte is 1%-8%.
[0052] In some embodiments, the core layer monomers used to synthesize the core layer include: o-phenylphenoxyethyl acrylate, and at least two or at least three of acrylonitrile, unsaturated carboxylic acid, acrylate, unsaturated amide, and styrene. The shell monomers used to synthesize the shell layer include at least two or at least three of unsaturated sulfonates, unsaturated hydroxy esters, unsaturated carboxylic acids, unsaturated sulfonates, unsaturated amides, unsaturated phosphates, and other monomers; Optionally, the unsaturated carboxylic acid is selected from at least one of acrylic acid, methacrylic acid, ethyl acrylic acid, propyl acrylic acid, isopropyl acrylic acid, n-butyl acrylic acid, isobutyl acrylic acid, tert-butyl acrylic acid, cyclopropyl acrylic acid, n-pentyl acrylic acid, isopentyl acrylic acid, cyclopentyl acrylic acid, n-hexyl acrylic acid, isohexyl acrylic acid, and cyclohexyl acrylic acid, or The acrylic acid ester is selected from at least one of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, cyclopropyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate, lauryl methacrylate, glycidyl methacrylate, tert-butylaminoethyl methacrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl acrylate, vinyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, phenyl methacrylate, dodecyl methacrylate, and hexadecyl methacrylate, or The unsaturated amide is selected from at least one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, N-methyl acrylamide and N-hydroxymethyl methacrylamide, or The unsaturated sulfonate is selected from at least one of styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, allyl sulfonate, methyl allyl sulfonate, and methacrylamide isopropyl sulfonate, or The unsaturated sulfonate is selected from at least one of methyl styrene sulfonate, ethyl styrene sulfonate, propyl styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, allyl sulfonate, methyl allyl sulfonate, and methacrylamide isopropyl sulfonate, or The unsaturated hydroxy ester is selected from at least one of β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, bis(2-hydroxyethyl) maleate, and 2-hydroxyethyl methyl fumarate, or The unsaturated phosphate is selected from at least one of di(2-methacryloyloxyethyl)phosphate, 2-hydroxyethyl methacrylate phosphate, 2-hydroxyethyl acrylate phosphate, and allyl polyether phosphate, or The other monomers are selected from at least one of polyethylene glycol acrylate, vinyl pyridine, vinyl pyrrolidone, polyethylene glycol methacrylate, ethylene glycol dimethacrylate, β-carboxyethyl acrylate, sodium 1-allyloxy-2-hydroxypropyl sulfonate, and diallyl maleate.
[0053] In some embodiments, the raw materials for preparing the negative electrode binder include: a core layer monomer for synthesizing the core layer, a shell layer monomer for synthesizing the shell layer, an initiator, an emulsifier and water. Wherein, the weight ratio of the shell monomer to the core monomer is (0.13-0.52): 1, or Based on 200 parts by weight of the total weight of the shell layer monomer and the core layer monomer, the weight of the emulsifier is 8-15 parts, or Based on the total weight of the shell layer monomer and the core layer monomer being 200 parts, the weight of the initiator is 10 parts, or Based on 200 parts by total weight of the shell layer monomer and the core layer monomer, the weight of the water is 500-1000 parts.
[0054] By controlling the relative amounts of raw materials such as the core layer monomer used to synthesize the core layer, the shell layer monomer used to synthesize the shell layer, the initiator, the emulsifier and water, the parameters such as the glass transition temperature of the negative electrode binder and the degree of swelling in the electrolyte are ensured to be within the above range, so that the negative electrode binder has good electrical properties.
[0055] The preparation method of the above-mentioned inorganic binder comprises the following steps: (1) adding a core layer monomer to an aqueous solution containing an emulsifier, mixing and heating the mixture once, and adding an initiator to react the mixture once; (2) Pre-emulsifying the shell monomer, emulsifier and water. After the pre-emulsification, add the pre-emulsified liquid and the aqueous solution of the initiator to the reaction product of (1) for secondary reaction. After cooling, the following is obtained: Figure 1 The negative electrode binder shown has a core-shell structure.
[0056] In some embodiments, the negative electrode binder is used to prepare a secondary battery, and the secondary battery includes a lithium ion battery or a sodium ion battery; Optionally, the negative electrode binder, the negative electrode current collector, the negative electrode material, and the conductive agent form a negative electrode, or the negative electrode binder, the negative electrode current collector, the negative electrode material, the conductive agent, and the thickener form a negative electrode sheet; Optionally, the negative electrode material is graphite, the conductive agent is Super-P, and the thickener is carboxymethyl cellulose.
[0057] In a third aspect, based on the above technical solution, an embodiment of the present invention further provides a negative electrode plate, on which the above negative electrode binder is loaded.
[0058] In a fourth aspect, an embodiment of the present invention, based on the above technical solution, further provides an electrochemical energy storage device, the electrochemical energy storage device comprising: the aforementioned negative electrode binder, or the aforementioned negative electrode sheet; Optionally, the electrochemical energy storage device includes a secondary battery, and the secondary battery includes a lithium-ion battery or a sodium-ion battery.
[0059] In order to enable those skilled in the art to clearly understand the above implementation details and operations of the present invention, the implementation scheme of the present invention is illustrated by specific examples below.
[0060] The following examples and comparative examples illustrate the present invention in more detail, but the present invention is not limited thereto. Moreover, "parts" and "%" in the examples and comparative examples represent parts by mass and % by mass, respectively, unless otherwise specified. Physical properties and performance evaluation tests of the lithium ion secondary battery electrode binders obtained in the examples and comparative examples and the batteries obtained using the electrode binders were conducted by the following methods. Example 1
[0061] This embodiment prepares a negative electrode binder, wherein the core layer monomer is o-phenylphenoxyethyl acrylate (whose chemical structure is as follows: Figure 2 As shown), acrylonitrile, methacrylic acid and ethyl acrylate, the shell monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell monomer to the core monomer is 0.20:1, and the emulsifier is 10 parts.
[0062] Prepare 200 parts of the above core layer monomer and shell layer monomer, 10 parts of initiator, 10 parts of emulsifier, 500-1000 parts of deionized water, and prepare the negative electrode binder according to the following steps: (1) adding a core layer monomer to an aqueous solution containing an emulsifier, mixing and heating the mixture once, and adding an initiator to react the mixture once; (2) Pre-emulsifying the shell monomer, emulsifier and water. After the pre-emulsification, add the pre-emulsified liquid and the aqueous solution of the initiator to the reaction product of (1) for secondary reaction. After cooling, the following is obtained: Figure 1 The negative electrode binder shown has a core-shell structure. Example 2
[0063] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.52:1, and the emulsifier is 15 parts. Others are the same as in Example 1. Example 3
[0064] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.16:1, and the emulsifier is 8 parts. Others are the same as in Example 1. Example 4
[0065] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.13:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Example 5
[0066] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.25:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Example 6
[0067] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and butyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Example 7
[0068] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, styrene and methyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Example 8
[0069] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Example 9
[0070] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, methacrylic acid amide and ethyl styrene sulfonate, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Example 10
[0071] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and isooctyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Embodiment 11
[0072] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid, methyl acrylate and butyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Example 12
[0073] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, acrylamide and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Embodiment 13
[0074] This embodiment prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, di(2-methacryloyloxyethyl) phosphate and N-hydroxymethyl acrylamide, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Comparative Example 1
[0075] In this comparative example, a negative electrode binder is prepared, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 1.25:1, and the emulsifier is 25 parts. Others are the same as in Example 1. Comparative Example 2
[0076] This comparative example prepared a negative electrode binder, wherein the core layer monomers were o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers were sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers was 0.08:1, and the emulsifier was 5 parts. Others were the same as in Example 1. Comparative Example 3
[0077] In this comparative example, a negative electrode binder is prepared, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.70:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Comparative Example 4
[0078] This comparative example prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the emulsifier is 10 parts, and no shell layer polymer is added. Others are the same as in Example 1. Comparative Example 5
[0079] This comparative example prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, acrylamide and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Comparative Example 6
[0080] This comparative example prepares a negative electrode binder, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, ethyl acrylate and butyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Comparative Example 7
[0081] In this comparative example, a negative electrode binder is prepared, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and butyl acrylate, the shell layer monomers are hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Other parts are the same as in Example 1. Comparative Example 8
[0082] In this comparative example, a negative electrode binder is prepared, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, methacrylamide and methacrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Comparative Example 9
[0083] In this comparative example, a negative electrode binder is prepared, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, butyl acrylate, methacrylic acid and acrylic acid, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Comparative Example 10
[0084] In this comparative example, a negative electrode binder is prepared, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, acrylic acid, methyl acrylate and butyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Comparative Example 11
[0085] In this comparative example, a negative electrode binder is prepared, wherein the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, butyl acrylate and vinyl pyrrolidone, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Comparative Example 12
[0086] In this comparative example, a negative electrode binder is prepared, wherein the core layer monomers are acrylonitrile, methacrylic acid and ethyl acrylate, the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid, the weight ratio of the shell layer monomers to the core layer monomers is 0.20:1, and the emulsifier is 10 parts. Others are the same as in Example 1. Performance Testing
[0087] (1) Take the negative electrode binders prepared in Examples 1-13 and Comparative Examples 1-12 and prepare negative electrode sheets respectively: According to the mass ratio, 96.5% of graphite, 1% of Super-P as a conductive agent, 1.5% of a negative electrode binder and 1% of CMC solution (thickener, prepared by dissolving carboxymethyl cellulose in water) are mixed, and then water is added and mixed again to prepare the negative electrode slurry. The slurry is applied to both sides of the 10μm thick Cu foil as a current collector in a manner of 120μm thickness after roller pressure treatment, dried at 100°C for 5 minutes, and pressed to form a negative electrode active material coating part. A negative electrode active material non-coating part without negative electrode active material coating is set on one end face of the two ends, and a negative electrode conductive sheet is installed to form a negative electrode.
[0088] (2) The negative electrode prepared in step (1) was assembled into a lithium-ion battery and the performance was tested. Table 1 shows the test results.
[0089]
[0090] As shown in the results in Table 1, the shell thickness and core diameter of Examples 1-5 and Comparative Examples 1-4 are different, and different shell thicknesses and core diameters correspond to different battery performances. The shell thickness and core diameter can be adjusted by adjusting the weight ratio of the shell monomer and the core monomer.
[0091] Among them, the weight ratio of the shell layer monomer and the core layer monomer in Example 1 is 0.2:1, the core diameter and the shell thickness are 255.3 nm and 7.8 nm respectively, the bonding force is normal, and the battery cycle performance is high.
[0092] The weight ratio of the shell monomer and the core monomer of Example 2 is 0.52:1, and the core diameter and shell thickness are 105.6nm and 8.0nm, respectively. Compared with Example 1, the weight ratio of the shell monomer and the core monomer of Example 2 is increased, so that the core becomes smaller and the shell thickness is normal, resulting in lower adhesion, higher modulus, and a slightly reduced number of cycles.
[0093] Compared with Example 1, the weight ratio of the shell monomer to the core monomer in Example 3 is reduced (0.16:1), resulting in a larger core thickness and a normal shell thickness, which leads to increased adhesion, reduced modulus, and reduced cycle life.
[0094] Compared with Example 1, the weight ratio of the shell layer monomer and the core layer monomer in Example 4 becomes smaller (0.13:1), so that the shell layer thickness is relatively small, which leads to a low elastic modulus, more significant expansion of the pole piece, and a short cycle life.
[0095] Compared with Example 1, the weight ratio of the shell layer monomer to the core layer monomer in Example 5 is increased (0.25:1), resulting in a thicker shell thickness and a normal core layer diameter, which leads to a larger modulus and a shorter lifespan.
[0096] Compared with Example 1, the weight ratio of the shell layer monomer and the core layer monomer of Comparative Example 1 becomes larger (1.25:1), the shell thickness is normal, the core thickness is very small, the bonding force is low, the modulus is large, the pole piece is tough, the pole piece expansion is slightly low, and the life is very short.
[0097] Compared with Example 1, the weight ratio of the shell layer monomer and the core layer monomer in Comparative Example 2 becomes smaller (0.08:1), the shell thickness is normal, the core thickness is very large, the bonding force is relatively large, the modulus is large, the pole piece has no toughness, the pole piece expands greatly, and the life is very short.
[0098] Compared with Example 1, the weight ratio of the shell layer monomer and the core layer monomer in Comparative Example 3 becomes larger (0.7:1), the core thickness is normal, the shell thickness is very large, the bonding force is relatively large, the modulus is very large, the pole piece is tough, the pole piece expands greatly, and the life is very short.
[0099] Compared with Example 1, Comparative Example 4 does not add shell monomers, the core layer diameter is normal, there is no shell layer, the bonding force is very small, the modulus is small, the pole piece has no toughness, the pole piece expands greatly, and the life is very short.
[0100] Based on the experimental results of Examples 1-5 and Comparative Examples 1-4, it can be concluded that when the diameter of the core layer is 50-500nm and the thickness of the shell layer is 1-10 nm, the negative electrode binder has both good flexibility and high elastic modulus, which can reduce the brittleness of the negative electrode sheet and effectively ensure the cycle stability. When the diameter of the core layer is less than 50nm, the flexibility of the negative electrode binder will be insufficient, which will easily lead to the prepared negative electrode sheet being brittle and easy to crack, and affect the cycle life; when the diameter of the core layer is greater than 500nm, the binder modulus is insufficient, the expansion inhibition ability is insufficient, and the cycle life is reduced. When the shell thickness is greater than 10nm, the negative electrode sheet will be brittle and easy to crack, and the cycle life will be affected; when the shell thickness is less than 1nm, the modulus is low, the expansion inhibition ability is reduced, and the cycle life is reduced.
[0101] As shown in the results of Table 1, the core layer glass transition temperature and the shell layer glass transition temperature of Examples 1, 6-9 and Comparative Examples 5-8 are different, and different core layer glass transition temperatures and shell layer glass transition temperatures correspond to different battery performances. Among them, the size of the core layer glass transition temperature and the shell layer glass transition temperature can be adjusted by adjusting the types of shell layer monomers and core layer monomers.
[0102] The core layer glass transition temperature and the shell layer glass transition temperature of the shell layer of Example 1 are 4.2 and 125.1 respectively, and the bonding force is normal and the battery cycle performance is high. The core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, and the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid.
[0103] The core layer glass transition temperature and shell layer glass transition temperature of Example 6 are -9.5 and 124.3 respectively. Compared with Example 1, the core glass transition temperature of Example 6 is lower, the bonding force of the negative electrode binder is slightly larger, the elastic modulus is too low, the pole piece expands too much, and the battery life is lower. In the core layer monomer, the ethyl acrylate in Example 1 is replaced by butyl acrylate.
[0104] The core layer glass transition temperature and shell layer glass transition temperature of Example 7 are 8.9 and 125.2 respectively. Compared with Example 1, the core glass transition temperature of Example 7 is higher, resulting in a slight decrease in the viscosity of the negative electrode binder, a larger elastic modulus, a slightly smaller expansion of the pole piece, and a lower cycle life. Among them, in the core layer monomer, methacrylic acid in Example 1 is replaced by styrene, and ethyl acrylate is replaced by methyl acrylate.
[0105] The core layer glass transition temperature and shell layer glass transition temperature of Example 8 are 4.2 and 102.2 respectively. Compared with Example 1, the shell glass transition temperature of Example 8 is lower, which has little effect on the viscosity of the negative electrode binder, the elastic modulus is slightly lower, the pole piece expands normally, and the cycle life is lower. Among them, hydroxybutyl methacrylate is deleted from the shell monomer relative to Example 1.
[0106] The core layer glass transition temperature and shell layer glass transition temperature of Example 9 are 4.2 and 138.1 respectively. Compared with Example 1, the shell glass transition temperature of Example 9 is higher, which has little effect on the viscosity of the negative electrode binder, the elastic modulus is slightly higher, the pole piece expansion is slightly higher, and the cycle life is lower. Among them, in the shell monomer, hydroxypropyl acrylate and acrylic acid are replaced by methacrylic acid amide and ethyl styrene sulfonate.
[0107] The core layer glass transition temperature and shell layer glass transition temperature of comparative example 5 are 29.5 and 125.1 respectively. Compared with example 1, the core glass transition temperature of comparative example 5 is very high, the viscosity is very low, the elastic modulus is very large, the pole piece has toughness, and the battery cycle life is short. Among them, in the core layer monomer, the methacrylic acid in example 1 is replaced by acrylamide.
[0108] The core layer glass transition temperature and shell layer glass transition temperature of comparative example 6 are -25.1 and 125.1 respectively. Compared with example 1, the core glass transition temperature of comparative example 6 is very low, the viscosity is normal, the elastic modulus is extremely low, the pole piece has no toughness, the pole piece expands greatly, and the battery cycle life is short. Among them, in the core layer monomer, the methacrylic acid in example 1 is replaced by butyl acrylate.
[0109] The core layer glass transition temperature and shell layer glass transition temperature of comparative example 7 are 4.2 and 65.3 respectively. Compared with example 1, the shell glass transition temperature of comparative example 7 is very low, the viscosity is low, the elastic modulus is extremely low, the pole piece has no toughness, the pole piece expands greatly, and the battery cycle life is very short. Among them, in the core layer monomer, the ethyl acrylate in example 1 is replaced by butyl acrylate; in the shell layer polymer monomer, the sodium styrene sulfonate in example 1 is deleted.
[0110] The core layer glass transition temperature and shell layer glass transition temperature of Comparative Example 8 are 4.2 and 178.8 respectively. Compared with Example 1, the shell glass transition temperature of Comparative Example 8 is very high, the viscosity is low, the elastic modulus is large, the pole piece is tough, the pole piece expansion is low, and the battery cycle life is very short. Among them, in the core layer monomer, the hydroxypropyl acrylate and acrylic acid in Example 1 are replaced by methacrylamide and methacrylic acid.
[0111] Based on the experimental results of Examples 1, 6-9 and Comparative Examples 5-8, it can be concluded that the shell layer has a higher glass transition temperature than the core layer, which can better maintain the morphology of the negative electrode binder during the operation of the lithium-ion battery, thereby better suppressing the expansion of the negative electrode pole piece and effectively extending the cycle life of the lithium-ion battery. When the glass transition temperature of the polymer of the core layer is -20°C to 20°C, and the glass transition temperature of the polymer of the shell layer is 80°C to 160°C, the negative electrode binder has both good flexibility and high elastic modulus, which can reduce the brittleness of the negative electrode piece and effectively ensure the cycle stability. When the glass transition temperature of the polymer of the core layer is less than -20°C, the modulus of the negative electrode binder will be insufficient, and the ability to suppress expansion will decrease; when the glass transition temperature of the polymer of the core layer is greater than 20°C, the flexibility is insufficient and the pole piece is prone to cracking. When the glass transition temperature of the shell is greater than 160°C, the electrode will become brittle and easy to crack, and the cycle life will be affected; when the glass transition temperature of the shell is less than 80°C, the expansion of the negative electrode will be inhibited, reducing the cycle life of the lithium-ion battery.
[0112] As shown in the results in Table 1, the swelling degree of the core layer in the electrolyte and the swelling degree of the shell layer in the electrolyte of Examples 1, 10-13 and Comparative Examples 9-11 are different, and the swelling degree of the core layer and the shell layer in different electrolytes corresponds to different battery performance. Among them, the swelling degree of the core layer in the electrolyte and the swelling degree of the shell layer in the electrolyte can be adjusted by adjusting the types of the polymer monomer of the shell layer and the polymer monomer of the core layer.
[0113] The swelling degree in the core layer electrolyte and the swelling degree in the shell layer electrolyte of Example 1 are 50.5% and 5.5% respectively, and the bonding force is normal and the battery cycle performance is high. Among them, the core layer monomers are o-phenylphenoxyethyl acrylate, acrylonitrile, methacrylic acid and ethyl acrylate, and the shell layer monomers are sodium styrene sulfonate, hydroxybutyl methacrylate, hydroxypropyl acrylate and acrylic acid.
[0114] The swelling degree in the core layer electrolyte and the swelling degree in the shell layer electrolyte of Example 10 are 35.5% and 5.5% respectively. Compared with Example 1, the core swelling is lower, the bonding force of the negative electrode binder is not greatly affected, the elastic modulus is higher, the pole piece expansion is lower, and the battery life is relatively normal. Among them, in the core layer monomer, the ethyl acrylate in Example 1 is replaced by isooctyl acrylate.
[0115] The swelling degree in the core layer electrolyte and the swelling degree in the shell layer electrolyte of Example 11 are 95.5% and 5.5% respectively. Compared with Example 1, the core swelling is higher, the bonding force of the negative electrode binder is not greatly affected, the elastic modulus is not greatly affected, the pole piece expansion is low, and the battery life is relatively normal. Among them, in the core layer monomer, the ethyl acrylate in Example 1 is replaced by methyl acrylate and butyl acrylate.
[0116] The swelling degree in the core layer electrolyte and the swelling degree in the shell layer electrolyte of Example 12 are 50.5% and 1.9% respectively. Compared with Example 1, the shell swelling is lower, the bonding force of the negative electrode binder is slightly reduced, and the battery life is relatively normal. Among them, in the shell monomer, the hydroxypropyl acrylate in Example 1 is replaced by acrylamide.
[0117] The swelling degree in the core layer electrolyte and the swelling degree in the shell layer electrolyte of Example 13 are 50.5% and 7.5%, respectively. Compared with Example 1, the shell swelling is higher, the bonding force of the negative electrode binder is slightly increased, the pole piece expansion is slightly increased, and the battery life is relatively normal. Among them, in the shell monomer, the hydroxypropyl acrylate and acrylic acid in Example 1 are replaced by: di(2-methacryloyloxyethyl) phosphate and N-hydroxymethyl acrylamide.
[0118] The swelling degree of the core layer electrolyte and the shell layer electrolyte of Comparative Example 9 are 13.2% and 5.5% respectively. Compared with Example 1, the core swelling is lower, the life is shorter, and other effects are not significant. Among them, in the core layer monomer, ethyl acrylate and acrylonitrile in Example 1 are replaced by butyl acrylate and acrylic acid.
[0119] The swelling degree of the core layer electrolyte and the shell layer electrolyte of Comparative Example 10 are 250.3% and 5.5% respectively. Compared with Example 1, the core swelling is larger, the bonding force is relatively normal, the modulus is low, the pole piece expansion is larger, and the life is extremely short. Among them, in the core layer monomer, the ethyl acrylate and methacrylic acid in Example 1 are replaced by acrylic acid, methyl acrylate, and butyl acrylate.
[0120] The swelling degree of the core layer electrolyte and the shell layer electrolyte of Comparative Example 11 are 50.5% and 20% respectively. Compared with Example 1, the shell swelling is larger, the bonding force is relatively normal, the modulus is normal, the pole piece expansion is larger, and the life is extremely short. Among them, in the shell polymer monomer, the hydroxypropyl acrylate and acrylic acid in Example 1 are replaced by vinyl pyrrolidone and butyl acrylate.
[0121] Based on the experimental results of Examples 1, 10-13 and Comparative Examples 9-11, it can be concluded that when the swelling degree of the core layer in the electrolyte is 20%-200% and the swelling degree of the shell layer in the electrolyte is 1%-10%, the negative electrode binder has both good flexibility and high elastic modulus, which can reduce the brittleness of the negative electrode sheet and effectively ensure the cycle stability. When the swelling degree of the core-shell electrolyte is less than 20%, it will lead to difficulties in ion transmission and large internal resistance, which will eventually affect the cycle life; when the swelling degree of the core layer electrolyte is greater than 200%, the ability to inhibit expansion decreases and the cycle life decreases. When the swelling degree of the shell layer electrolyte is less than 1%, ion transmission is difficult and the internal resistance is large; when the swelling degree of the shell layer electrolyte is greater than 10%, the ability to inhibit expansion decreases and the cycle life decreases.
[0122] Compared with Example 1, the core layer monomer of Comparative Example 12 does not contain o-phenylphenoxyethyl acrylate, and its bonding strength is poor and the battery cycle life is poor. Therefore, o-phenylphenoxyethyl acrylate, as one of the core layer monomers, contributes greatly to the improvement of bonding strength and can effectively improve the bonding effect and cycle life of the adhesive.
[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A negative electrode binder, characterized in that: The negative electrode binder has a core-shell structure, the core-shell structure consists of a core layer and a shell layer, and the shell layer covers the core layer; Wherein, the core layer monomer used to synthesize the core layer includes: o-phenylphenoxyethyl acrylate.
2. The negative electrode binder according to claim 1, characterized in that The core layer monomers used to synthesize the core layer include: o-phenylphenoxyethyl acrylate, and at least two or at least three of acrylonitrile, unsaturated carboxylic acid, acrylate, unsaturated amide, and styrene. The shell monomers used to synthesize the shell layer include at least two or at least three of unsaturated sulfonates, unsaturated hydroxy esters, unsaturated carboxylic acids, unsaturated sulfonates, unsaturated amides, unsaturated phosphates, and other monomers.
3. The negative electrode binder according to claim 2, characterized in that: The unsaturated carboxylic acid is selected from at least one of acrylic acid, methacrylic acid, ethyl acrylic acid, propyl acrylic acid, isopropyl acrylic acid, n-butyl acrylic acid, isobutyl acrylic acid, tert-butyl acrylic acid, cyclopropyl acrylic acid, n-pentyl acrylic acid, isopentyl acrylic acid, cyclopentyl acrylic acid, n-hexyl acrylic acid, isohexyl acrylic acid, and cyclohexyl acrylic acid; and / or The acrylic acid ester is selected from at least one of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, cyclopropyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate, lauryl methacrylate, glycidyl methacrylate, tert-butylaminoethyl methacrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl acrylate, vinyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, phenyl methacrylate, dodecyl methacrylate, and hexadecyl methacrylate; and / or The unsaturated amides are selected from at least one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, N-methyl acrylamide and N-hydroxymethyl methacrylamide; and / or The unsaturated sulfonate is selected from at least one of styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, methyl allyl sulfonate, allyl sulfonate, and methacrylamide isopropyl sulfonate; and / or The unsaturated sulfonate is selected from at least one of methyl styrene sulfonate, ethyl styrene sulfonate, propyl styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, allyl sulfonate, methyl allyl sulfonate, and methacrylamide isopropyl sulfonate; and / or The unsaturated hydroxy ester is selected from at least one of β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, bis(2-hydroxyethyl)maleate, and 2-hydroxyethyl methyl fumarate; and / or The unsaturated phosphate is selected from at least one of di(2-methacryloyloxyethyl)phosphate, 2-hydroxyethyl methacrylate phosphate, 2-hydroxyethyl acrylate phosphate, and allyl polyether phosphate; and / or The other monomers are selected from at least one of polyethylene glycol acrylate, vinyl pyridine, vinyl pyrrolidone, polyethylene glycol methacrylate, ethylene glycol dimethacrylate, β-carboxyethyl acrylate, sodium 1-allyloxy-2-hydroxypropyl sulfonate, and diallyl maleate.
4. The negative electrode binder according to claim 1, characterized in that The raw materials for preparing the negative electrode binder include: a core layer monomer for synthesizing the core layer, a shell layer monomer for synthesizing the shell layer, an initiator, an emulsifier and water; Wherein, the weight ratio of the shell monomer to the core monomer is (0.13-0.52): 1, or Based on 200 parts by weight of the total weight of the shell layer monomer and the core layer monomer, the weight of the emulsifier is 8-15 parts, or Based on the total weight of the shell layer monomer and the core layer monomer being 200 parts, the weight of the initiator is 10 parts, or Based on 200 parts by total weight of the shell layer monomer and the core layer monomer, the weight of the water is 500-1000 parts.
5. The negative electrode binder according to any one of claims 1 to 4, characterized in that The diameter of the core layer is 50-500 nm, and the thickness of the shell layer is 1-10 nm; and / or The glass transition temperature of the core layer is -20°C to 20°C, and the glass transition temperature of the shell layer is 80°C to 160°C; and / or The swelling degree of the core layer in the electrolyte is 20%-200%, and the swelling degree of the shell layer in the electrolyte is 1%-10%.
6. The negative electrode binder according to any one of claims 1 to 4, characterized in that The glass transition temperature of the shell layer is greater than the glass transition temperature of the core layer; and / or The negative electrode binder is used to prepare a secondary battery, and the secondary battery includes a lithium ion battery or a sodium ion battery.
7. A negative electrode binder, characterized in that The negative electrode binder has a core-shell structure, the core-shell structure consists of a core layer and a shell layer, and the shell layer covers the core layer; wherein the diameter of the core layer is 50-500 nm, the thickness of the shell layer is 1-10 nm, or The glass transition temperature of the shell layer is greater than the glass transition temperature of the core layer, or The swelling degree of the core layer in the electrolyte is 20%-200%, and the swelling degree of the shell layer in the electrolyte is 1%-10%.
8. The negative electrode binder according to claim 7, characterized in that The diameter of the core layer is 50-500 nm, and the thickness of the shell layer is 1-10 nm; and / or The glass transition temperature of the core layer is -20°C to 20°C, and the glass transition temperature of the shell layer is 80°C to 160°C; and / or The swelling range of the core layer in the electrolyte is 20%-200%, and the swelling range of the shell layer in the electrolyte is 1%-10%.
9. The negative electrode binder according to claim 7, characterized in that: The core layer monomers used to synthesize the core layer include: o-phenylphenoxyethyl acrylate.
10. The negative electrode binder according to any one of claims 7 to 9, characterized in that: The core layer monomers used to synthesize the core layer include: o-phenylphenoxyethyl acrylate, and at least two or at least three of acrylonitrile, unsaturated carboxylic acid, acrylate, unsaturated amide, and styrene, or The shell monomers used to synthesize the shell layer include at least two or at least three of unsaturated sulfonates, unsaturated hydroxy esters, unsaturated carboxylic acids, unsaturated sulfonates, unsaturated amides, unsaturated phosphates, and other monomers.
11. The negative electrode binder according to claim 10, characterized in that: The unsaturated carboxylic acid is selected from at least one of acrylic acid, methacrylic acid, ethyl acrylic acid, propyl acrylic acid, isopropyl acrylic acid, n-butyl acrylic acid, isobutyl acrylic acid, tert-butyl acrylic acid, cyclopropyl acrylic acid, n-pentyl acrylic acid, isopentyl acrylic acid, cyclopentyl acrylic acid, n-hexyl acrylic acid, isohexyl acrylic acid, and cyclohexyl acrylic acid; and / or The acrylic acid ester is selected from at least one of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, cyclopropyl acrylate, isooctyl acrylate, hydroxypropyl acrylate, 2-hydroxyethyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, isooctyl methacrylate, hydroxypropyl methacrylate, 2-hydroxyethyl methacrylate, lauryl methacrylate, glycidyl methacrylate, tert-butylaminoethyl methacrylate, dimethylaminoethyl methacrylate, tert-butylaminoethyl acrylate, vinyl methacrylate, cyclohexyl methacrylate, benzyl methacrylate, phenyl methacrylate, dodecyl methacrylate, and hexadecyl methacrylate; and / or The unsaturated amides are selected from at least one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N,N-dimethyl acrylamide, N-methyl acrylamide and N-hydroxymethyl methacrylamide; and / or The unsaturated sulfonate is selected from at least one of styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, methyl allyl sulfonate, allyl sulfonate, and methacrylamide isopropyl sulfonate; and / or The unsaturated sulfonate is selected from at least one of methyl styrene sulfonate, ethyl styrene sulfonate, propyl styrene sulfonate, 2-acrylamido-2-methylpropane sulfonate, vinyl sulfonate, methyl allyl sulfonate, allyl sulfonate, and methacrylamide isopropyl sulfonate; and / or The unsaturated hydroxy ester is selected from at least one of β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, bis(2-hydroxyethyl)maleate, and 2-hydroxyethyl methyl fumarate; and / or The unsaturated phosphate is selected from at least one of di(2-methacryloyloxyethyl)phosphate, 2-hydroxyethyl methacrylate phosphate, 2-hydroxyethyl acrylate phosphate, and allyl polyether phosphate; and / or The other monomers are selected from at least one of polyethylene glycol acrylate, vinyl pyridine, vinyl pyrrolidone, polyethylene glycol methacrylate, ethylene glycol dimethacrylate, β-carboxyethyl acrylate, sodium 1-allyloxy-2-hydroxypropyl sulfonate, and diallyl maleate.
12. The negative electrode binder according to any one of claims 7 to 9, characterized in that: The negative electrode binder is used to prepare a secondary battery, and the secondary battery includes a lithium ion battery or a sodium ion battery.
13. The negative electrode binder according to any one of claims 7 to 9, characterized in that: The raw materials for preparing the negative electrode binder include: a core layer monomer for synthesizing the core layer, a shell layer monomer for synthesizing the shell layer, an initiator, an emulsifier and water; Wherein, the weight ratio of the shell monomer to the core monomer is (0.13-0.52): 1, or Based on 200 parts by weight of the total weight of the shell layer monomer and the core layer monomer, the weight of the emulsifier is 8-15 parts, or Based on the total weight of the shell layer monomer and the core layer monomer being 200 parts, the weight of the initiator is 10 parts, or Based on 200 parts by total weight of the shell layer monomer and the core layer monomer, the weight of the water is 500-1000 parts.
14. A negative electrode plate, characterized in that: The negative electrode sheet is loaded with the negative electrode binder according to any one of claims 1 to 13.
15. An electrochemical energy storage device, characterized in that: The electrochemical energy storage device comprises: the negative electrode binder according to any one of claims 1 to 13, or the negative electrode plate according to claim 14.
16. The electrochemical energy storage device according to claim 15, characterized in that: The electrochemical energy storage device comprises a secondary battery, and the secondary battery comprises a lithium ion battery or a sodium ion battery.
Citation Information
Patent Citations
Negative electrode binder with core-shell structure as well as preparation method and application of negative electrode binder
CN116169292A
Negative electrode binder, negative electrode composition, negative electrode plate and lithium ion battery thereof
CN118448635A
Binder, binder composition, preparation method, negative electrode slurry, negative electrode plate, secondary battery, battery module, battery pack and electrical apparatus
US20240372100A1
Binder, electrode comprising same, secondary battery comprising same, capacitor comprising same, and preparation method for binder
WO2024111719A1
Core-shell type lithium-containing polyacrylic water-based adhesive, and preparation method therefor and use thereof
WO2024207816A1
Cited By
Negative electrode binder, negative electrode plate and electrochemical energy storage device
CN120590891A
Comb-shaped polymer binder, pole piece and battery
CN121203613A
A comb-like polymer binder, pole piece and battery
CN121203613B